The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/08998280.2014.11929052
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Macronutrient Intake of a Female Vegan Cyclist During an 8-Day Mountain Bike Stage Race

Abstract: This report describes the dietary intake of a vegan mountain biker (height, 161 cm; weight, 49.6 kg; body mass index, 19.1 kg/m(2); relative peak power output, 4.6 W/kg) during the Transalp Challenge 2004 (altitude climbed, 22,500 m; total distance, 662 km), illustrating an aggressive dietary strategy that allowed the cyclist to be competitive. She finished the 8-stage event in 42 hours (mixed category, rank 16; 514 minutes behind the winners of this category), cycling with an average heart rate of 79.5% of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 7 publications
4
22
0
Order By: Relevance
“…Additionally, recent case studies have also highlighted the capabilities of prominent vegan endurance athletes [115,116]. A case study by Wirnitzer and Kornexel (2017) reported energy intake and performance data for a female vegan cyclist competing in the 8-day Transalp Challenge 2004 (662 km, total altitude: 22,500 m).…”
Section: Exercise Performance and Plant-based Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent case studies have also highlighted the capabilities of prominent vegan endurance athletes [115,116]. A case study by Wirnitzer and Kornexel (2017) reported energy intake and performance data for a female vegan cyclist competing in the 8-day Transalp Challenge 2004 (662 km, total altitude: 22,500 m).…”
Section: Exercise Performance and Plant-based Dietsmentioning
confidence: 99%
“…Percent of peak power output and heart rate maximum were monitored continuously during the race. Over the course of the race, her body weight remained stable, indicating appropriate fueling and hydration practices, and she finished in 16th place out of 64 teams in the mixed category, meeting her goal of finishing in the top 20 [115].…”
Section: Exercise Performance and Plant-based Dietsmentioning
confidence: 99%
“…To date, the impact of a plant-based diet on athletic performance is not clearly understood. Recent case reports showed that even vegan athletes can reach top athletic performances [21, 22]. Other studies dealing with a vegetarian and vegan diet related to sport are questionnaire-based and do not include nutritional or sports medical diagnostics [4, 5, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated plant‐based dietary patterns and endurance performance, but these have small sample sizes with cross‐sectional study designs (Hanne et al 1986; Nieman et al 1989; Nebl et al 2019) or are case studies (Leischik & Spelsberg 2014; Wirnitzer & Kornexl 2014). Deriving conclusions pertaining to the ability of a plant‐based diet to modulate endurance performance from these studies would be disingenuous as natural differences in physiology between groups could influence the results irrespective of diet.…”
Section: Specific Endurance Testing and Plant‐based Dietsmentioning
confidence: 99%